The Conception of Sharia Fintech Lending and Its Regulatory Preparedness in Indonesia - Fikriawan, Suad; Ayu, Diyan Putri; Nafi'ah, Nafi'ah (Indonesian Journal of Islamic Economics and Finance, 2023)
This study aims to describe the concept of Sharia Fintech Lending and its regulatory readiness in Indonesia. Along with the development of technology and online lending issues that are troubling the public, sharia fintech lending grows and develops. However, the challenges of online lending make this industry little known to the public, so its development tends to be slow. In quantitative terms, this industry is not as much as conventional fintech. Therefore the government (OJK) initiated regulations for this industry supported by the DSN MUI Fatwa. However, after it was implemented, it turned out that there were many obstacles that hindered the growth of sharia fintech lending. Based on the research findings, OJK needs to review this regulation to make it more flexible and support the development of Islamic banking fintech more rapidly